IMPLEMENTASI BIMBINGAN KARIR DALAM MENCAPAI PRESTASI KERJA KARYAWAN DI RESTORAN LOMBOK IDJO YOGYAKARTA - Husni Ismail (Hikmah, 2017)
Facing the challenge of globalization today, employees as human resources who have the ability, attitudes, values, needs, and characteristics must get great attention in an organization or company. Through guidance in the form of education and training can be viewed as one invesment, so that any organization or company that wants to grow and develop requires guidance for employees. This study aims to determine the implementation of career guidance in achieving employee performance in restaurants Lombok Idjo Yogyakarta. Understanding of career becomes important for employees in achieving targets and goals set by the company. By running the duties and responsibilities as employees will result in employee performance. Work is not just about getting money or economical course. But many things that make employees able to survive and continue to perform their duties as workers. Career concept and understanding is given by the management in the form of guidance in the form of individual and group. This research method uses qualitative research that describes the phenomenon that appears in the field. The data collection conducted by researchers are : observation, interviews, and documentation to obtain valid and accurate data. The results of this study indicate that there is a significant influence of career guidance on employee performance is given by the management. Achievement of position and promotion of office due to the achievement shown by employees through the attitude and good skills and duties and responsibilities carried out by employees during work in Lombok Idjo Yogyakarta.Keywords : career guidance, employee performance